Peningkatan Model Pembelajaran Jigsaw Pada Mata Pelajaran Bahasa Indonesia Terhadap Hasil Belajar Siswa Kelas 3 SD - Khalsani Mutia Nadia Husna Kembaren; Rahma Zikriya Hulwa Ali; Renni Ramadhani Lubis (BADAN PENERBIT STIEPARI PRESS, 2024)
Weaknesses in the implementation of the learning process must be addressed through conducting an action research. This prompted the researcher to conduct a class action research. The research aimed to improve the learning process as well as to increase students' learning achievement. The subject of the research was 3rd grade students. While the object of research is Indonesian language learning achievement. Learning achievement data was collected through learning achievement tests and then analysed using descriptive analysis. Success criteria: class average score of at least 75 and classical completeness of at least 85%. The initial data only reached a score of 68.12 with 45% learning completeness, in cycle I it rose to 79.36 with 75% learning completeness, and in cycle II it rose to 88.21 with 97% learning completeness. The data in cycle II shows that the expected success has been achieved and has even exceeded the success indicators of the proposed research study. Thus, the researcher concluded that the jigsaw type cooperative learning model applied in the learning process was able to improve the Indonesian language learning achievement of grade 3 students.